INOVASI REFLEKTOR PEMBATAS JALAN BERBASIS MATERIAL LOKAL UNTUK MITIGASI KECELAKAAN LALU LINTAS DI DESA SINDANGLAYA - Rahmat Mulya Nugraha; Irpan Nudin; M Hilmy Alzamzamy; Azka Aqila Qolbi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Road traffic safety on rural roads with hilly topography in Sindanglaya Village, Ciamis Regency, remains a significant concern due to the high risk of accidents, particularly at night when road visibility is limited. This community service program aimed to improve road user safety through the development and implementation of road-edge reflectors made from locally available materials that are affordable, practical, and sustainable. The program employed a participatory approach by actively involving community members in the planning, production, installation of reflectors, and traffic safety awareness activities. The results demonstrated that the installed reflectors significantly enhanced nighttime road visibility and enabled road users to identify road boundaries more clearly. In addition, the program successfully increased public awareness of the importance of safe driving practices. These findings indicate that appropriate technology based on local resources can serve as an effective and sustainable solution for reducing accident risks and improving road safety in rural areas.